Contribuição ao estudo de técnicas de acionamento e controle aplicadas ao gerador de relutância variável - Osorio, Caio Ruviaro Dantas (2017)
This master thesis presents the study of a generation system based on switched reluctance generators. This machine presents as characteristics simple structure, mechanical robustness, wide range of speed, low cost, high starting torque and fault tolerance capability. These features make this kind of machine a viable candidate for several systems demanding variable speed. Considering applications such as isolated wind power generation, aircraft and automobiles, the output voltage control is essential since, besides the speed, the power demand tends to oscillate sharply. In this context, voltage control techniques and the need for distinct drive systems considering different rotor speeds are analyzed, of which hysteresis current regulator (below base speed) and single pulse technique (above base speed) are highlighted. For both cases, PI controllers are designed based on first order estimated models. Considering the hysteresis regulator, a sliding mode controller is designed based on state space modelling. A simulation model considering magnetic saturation is obtained from experimental data, and an experimental platform is built for drive and control of the switched reluctance machine. In this sense, the techniques performance are evaluated through simulation and experimental results.